Evaluation the Effect Of Magnetized Water On The Bone Density And Osteoporosis In The Experimental Rats By DXA-Scan - Nour Abd Alrazaq Hassan; Tahseen Hussain Mubarak; Nameer Fadhel Gheaeb (Diyala Journal of Medicine, 2019)
Background: The electromagnetic field used with industrial, and also simultaneous action of those fields on the intensity of bone turnover process in rats was estimated by means of analysis of densitometry. The obtained effect was dependent on frequency and power density of used electromagnetic fields  .There was improved in quality of the water when exposed to the electromagnetic field with significant changes in the minerals and organic matter .Therefore it’s penetration into cell wall would be facilitated, which can accelerate ordinary diffusion of water. That is vital for growth and development of different organs .Exposing the water to strong magnetic fields affect in the water`s mineral content , and its effects depended on the "strength of the magnetic field and exposure time".